CONTRIBUTION OF COMMUNITY TO DEVIANT BEHAVIORS AMONG SECONDARY SCHOOL STUDENTS IN TRANS-NZOIAWEST SUB-COUNTY, KENYA - Mideva, Mugami Margaret; Emily, Dr. Kirwok; David, Dr. Nguti (IJRDO- Journal of Educational Research, 2016)
Deviant behaviors among secondary school going populations, the world over, are of concern toeducators, counselors and psychologists. This is because of the potential of deviant behaviors at theadolescent stage to undermine the achievement of both personal and national goals. Your socialenvironment including your family, friends, school, and neighborhood influence your behavior. Thisstudy assessed the contribution of social institutions (community) to deviant behaviors amongsecondary school students. The study was anchored on the Social-control Theory by Travis (1960)and Attachment Theory by Bowlby and Ainsworth (1991). Descriptive survey design was usedbecause the deputy head teachers’ guidance and counseling teachers’ and students’ attitudes weresought. The target population was 6529 respondents. The sample size was 661 respondents. SimpleRandom Sampling was used to select the schools and the students. Stratified Sampling was used toselect the zones then Purposive Sampling was used to select deputy principals and guidance andcounseling teachers. The researcher used questionnaires and behavior assessment tool as theinstruments to collect qualitative and quantitative data necessary for this study. The study wascarried out in Trans-Nzoia West Sub-County. Reliability was established by test-retest method in apilot study done in the neighboring sub-county. Validity was established by giving the instruments tothe experts in research field. Content validity was adopted for this study. Descriptive techniques ofdata analysis such as frequencies, percentages, means and standard deviations were used. Toestablish the relationship, Spearman’s rank was employed while t-tests were used to test forsignificance. The data was subjected to Statistical Package for Social Sciences version 17 for furtheranalysis. The study revealed the following: that the frequency of deviance in schools is low in thestudy area. The community contributes to deviant behaviors by having poor neighborhoods, highrates of violence lack of community norms and a culture of impunity in the society. Also, there is asignificant negative relationship between community and deviant behaviors among students. Thestudy recommended that the Ministry of Education should ensure that each school has a counselingroom and all guidance and counseling teachers be exposed to workshops and seminars to enablethem be effective in their work.